The effectiveness of health education programme on knowledge and attitude on cervical cancer prevention and human papillomavirus (HPV) vaccination among secondary school girls in Kota Bharu, Kelantan - Ismail, Nor Fatma (2018)
Introduction: Cervical cancer ranks as the third most frequent cancer among women in Asia and second in Malaysia after breast cancer. Malaysia introduced school-based National HPV prophylaxis vaccination programme started in 2010 to the girls aged 13 years old. However, many studies reported that adolescents had poor knowledge about cervical cancer and HPV vaccination with no standardised education module provided. The aim of our study is to determine the effectiveness of health education intervention in increasing the knowledge and attitude on cervical cancer prevention and HPVvaccination among students in Kelantan. Methodology: This is an open, non-randomised interventional study with control performed between April and August 2015 using multi-stage cluster sampling among female students in two secondary schools in Kota Bharu, Kelantan.The intervention group received health education programme about HPV vaccination and cervical cancer. It was delivered in Malay language by a trained-personnel consists of health talk with PowerPoint presentation, video show, flip chart and interactive presentation as well as equipped with related references. The students from control group received the standard education materials. A self-administered validated questionnaire was used for evaluation of the effectiveness of intervention on knowledge and attitude score at the baseline and at 3 months. Data were analyzed using SPSS version 22. Results: A total of 198 Malay female students was involved with equal number of subjects. Of those, 176 of them responded to post-test evaluation with 88.8% response rate. At the baseline, the mean (SD) of knowledge percentage score in intervention group was 44.9 (18.66) and for control group was 47.2 (15.29). Attitude mean (SD) percentage score in intervention group was 69.86 (10.43) and 66.37 (9.18) in control group. Mean knowledge percentage score within each group based on time at baseline and 3 months shows the mean difference (95% CI) was 12.23 (16.48,7.98) for intervention group and 3.80 (0.77,6.83) for control group. Post intervention, the estimated marginal mean (EMM) (95% CI) for knowledge percentage score was 57.6 (49.12,60.71) in the intervention group and 50.63 (47.81,53.47) in the control group. Respectively, the EMM (95% CI) for attitude percentage score was 70.3 (68.32,72.70) in the intervention group and 66.3 (64.09,68.59) in the control group. The mean difference between groups at baseline and 3 months was statistically significant for knowledge (P=0.001) but not for attitude (P=0.870). Conclusion: The new health education intervention has been shown to increase the knowledge on cervical cancer and HPV vaccination among the girls. However, it is not effective in increasing the attitude score when compared to the current standard health education practice. This new health education intervention could be used as culturallycompetent intervention and as the standard education module to improve the current education practice by school health unit. In addition, this could assist the health staff and paramedics in delivering health education to the students about cervical cancer and HPV vaccination.